Propofol Effect on Stress Response and Free Radicals in Patient during Surgery and Sedation Procedure - Theresia Monica Rahardjo (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Propofol is an intravenous anesthetic used worldwide as an anesthesia induction and maintenance agent. Propofol also used as sedation agent in Intensive Care Unit (ICU). Despite it’s usual anesthesia properties, propofol has an unique pharmacologic characteristic, especially as antioxidant and stress response reduction. These advantages suggested propofol has positive effects when used as an anesthesia agent in surgery or sedation in ICU in conditions when high stress and free radical level are released.CONTENT:Stress response and free radical can be elevated in various conditions including surgery or during care in ICU, especially critical ill patient. Cortisol is a major stress hormone that influences metabolism, cardiovascular and central nervous system, either in acute or chronic phase. Oxidative stress was marked by free radical elevation called Radical Oxygen Species (ROS). Combination of both elements (cortisol and ROS) can worsen patient condition. Propofol with anti-stress and antioxidant properties could be used to reduce stress response and attenuate free radical level in order to improve patient condition.SUMMARY: The anti-stress and antioxidant properties of Propofol are interesting, because these benefits can be added as adjunctive therapy when propofol was used as an anesthetic agent in surgery and a sedation in ICU.KEYWORDS: propofol, stress response, antioxidant